Assessment of Inappropriate Dose Adjustment of Antimicrobials and Other Medicines Among Chronic Kidney Disease Patients: A Multicenter Observational Study - Roheena Zafar; Inayat Ur Rehman; Yasar Shah; Khang Wen Goh; Long Chiau Ming (Progress in Microbes and Molecular Biology)
Most drugs undergo metabolism and elimination primarily by the kidneys. Consequently, drug dosages are largely contingent upon kidney function and require careful adjustment in patients with compromised renal function. Inaccurate dosage adjustments can lead to toxicities, therapeutic failures, and adverse drug reactions. This study sought to assess the appropriateness of dose adjustments for antimicrobials and other medicines among patients with Chronic Kidney Disease (CKD) attending both a public and a private hospital. A multicenter, retrospective observational study was carried out from January 1st to February 28th, 2023, among hospitalized CKD patients in two distinct facilities: Northwest General Hospital & Research Centre (a private institution) and the Institute of Kidney Diseases, Peshawar, Pakistan (a public institution). The goal was to compare adherence to dosing guidelines and to identify factors contributing to incorrect renal dose adjustments for antimicrobials and other medications. The study incorporated 358 CKD patients, with 179 patients from each hospital. Medications necessitating dosage adjustments were more frequently prescribed in the private hospital (n=515) compared to the public one (n=368). Nonetheless, dosages were more accurately adjusted in the private hospital (52.6%) than in the public hospital (40.5%). Of all the prescribed medications, 71.1% of antimicrobials in both hospitals were inaccurately adjusted. Multivariate logistic regression analysis showed that the number of drugs requiring adjustment (AOR=0.6; p=0.001) was independently correlated with inappropriate drug adjustments in the private hospital. Conversely, in the public hospital, both the number of drugs requiring adjustment (AOR=0.6; p=0.019) and the length of hospital stay (AOR=0.8; p=0.048) were independently linked with inappropriate drug adjustments. The research revealed that a significant number of hospitalized CKD patients receive inappropriate drug dosages, especially in public hospitals. This predisposes these patients to heightened risks, including therapeutic failure.